KUALITAS AIR DAERAH KJA DAN NON KJA DI WADUK JATIGEDE - Melati Taufanputri; Zahidah Zahidah; Heti Herawati; Mochamad Candra Wirawan Arief (Universitas Mataram, 2024)
The rapid development of fish farming using the Floating Net Cage (KJA) system has raised concerns about the water quality of the reservoir. This study aims to evaluate the water quality in KJA and non-KJA areas of the Jatigede Reservoir based on the physical-chemical parameters of the water. Analysis was conducted at four stations with varying levels of KJA activity. The results showed that, based on Government Regulation No. 22 of 2021, the pH and BOD parameters have exceeded the established quality standards. However, Jatigede Reservoir is still considered suitable for fisheries activities as other water quality parameters remain within the standards for Class II and III water. This study is expected to serve as a basis for the sustainable management of Jatigede Reservoir, aiming to mitigate the negative impacts of KJA on water quality while supporting its utilization as an economic livelihood resource for the local community.